MEDIATION EFFECT OF JOB SATISFACTION ON ORGANIZTIONAL CITIZENSHIP BEHAVIOUR - Leo Tri Hartantyo; Erita Yuliaseti Diah Sari; Herlina Siwi Widiana (Jurnal Psikologi Integratif, 2019)
An organization always need good employees to achieve the goals, Willingness to work optimally, being able to volunteer to work, not just fixing on his duties and responsibilities as a member of the organization becomes important. This research aims to look at the effect of job satisfaction in mediating the relationship between Islamic work ethics (IWE) and perceived organizational support (POS) on Organizational Citizenship Behavior (OCB). A total 64 manufacturing company employees participated in the study. The results showed that job satisfaction can be a mediator between IWE and POS on OCB. It was found that the effect of IWE on OCB directly is more significant than indirect relationship. Conversely, impact of POS on OCB indirectly is more significant than direct relationship. This means that without job satisfaction POS can significantly influence OCB.